Research on the theory of entrepreneurship Innovation at the individual level - Mei, Bai (E3S web of conferences, 2021)
In recent years, entrepreneurship has increasingly become a hot topic for scholars to study innovation and other fields from the perspective of entrepreneurship, especially the research on the characteristics of entrepreneurship and the mechanism of innovation. These scholars are interested in innovation. Starting from the concept of entrepreneurship and the theory of entrepreneurship at the individual level, this paper discusses the innovation mechanism of entrepreneurship by summarizing and combing the research results of entrepreneurship at home and abroad. Based on the analysis of relevant theories, this paper enriches the relevant theories of entrepreneurship and innovation, and lays a theoretical foundation for exploring the research of entrepreneurship that affects innovation.